Regulation of acetylated tubulin/Na +,K +-ATPase interaction by l-glutamate in non-neural cells: involvement of microtubules - Casale, César H.; Previtali, Gabriela; Serafino, Juan J.; Arce, Carlos A.; Barra, Héctor S. (Biochimica et biophysica acta, 2005)
A subpopulation of membrane tubulin consisting mainly of the acetylated isotype is associated with Na +,K +-ATPase and inhibits the enzyme activity. We found recently that treatment of cultured astrocytes with l-glutamate induces dissociation of the acetylated tubulin/Na +,K +-ATPase complex, resulting in increased enzyme activity. We now report occurrence of this phenomenon in non-neural cells. As in the case of astrocytes, the effect of l-glutamate is mediated by its transporters and not by specific receptors. In COS cells, the effect of l-glutamate was reversed by its elimination from culture medium, provided that d-glucose was present. The effect of l-glutamate was not observed when Na + was replaced by K + in the incubation medium. The ionophore monensin, in the presence of Na +, had the same effect as l-glutamate. Treatment of cells with taxol prevented the dissociating effect of l-glutamate or monensin. Nocodazole treatment of intact cells or isolated membranes dissociated the acetylated tubulin/Na +,K +-ATPase complex. The dissociating effect of nocodazol does not require Na +. These results indicate a close functional relationship among Na +,K +-ATPase, microtubules, and l-glutamate transporters, and a possible role in cell signaling pathways.